Flow rate in 2D silo discharge of binary granular mixtures: the role of ordering in monosized systems - Carlevaro, C. Manuel; Kozlowski, Ryan; Pugnaloni, Luis A. (Frontiers in Soft Matter, 2024)
A long-standing debate regarding the dynamics of silo discharge revolves around the use of mono-dispersed circular or spherical grains in simplified two-dimensional models. It is well-known that granular systems composed of particles of the same size can generate crystal or quasi-crystal domains with specific structural and dynamic behaviors. Can this ordering affect the flow rate to an extent that monosized systems cannot be good models for realistic materials? In this work, we present simulations of the discharge of two-dimensional silos filled with binary mixtures of circular grains that conserve the same mean particle size. We address the question of how ordering affects the mass flow rate, in particular considering the limit of mono-sized systems. We find that the typical hexagonal order observed does not affect the flow rate significantly. However, the flow rate does exhibit a weak, nonmonotonic dependence on packing bidispersity that correlates with changes in the outpouring speed of grains in the vicinity of the orifice.